INNOVATION AND CREATIVITY IN GAMELAN MANDOLIN - Mawan, I Gede; Kusuma, Putu Sandra Devindriati (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Gamelan Mandolin is a type of traditional Balinese music that is played by plucking. The Mandolin gamelan, which is thought to have originated from China, is still preserved by the people of Pupuan Village, Tabanan. One form of application of creativity and innovation in the world of music is in the development of the mandolin gamelan. Gamelan mandolin is a form of musical experiment that combines Balinese gamelan instruments with the mandolin, a musical instrument originating from China. In the creation process, the mandolin gamelan presents new challenges in terms of playing techniques, harmony and timbre which are different from gamelan in general. This article aims to examine the creativity of musicians in designing and processing gamelan mandolin instruments, as well as how these innovations have had an impact on the development of traditional and contemporary Balinese music. Using a composition and performance analysis approach, this research shows that the mandolin gamelan is not just a musical experiment, but also a means of enriching the Indonesian musical repertoire through mixing different cultural elements. Through creativity and innovation in the development of the mandolin gamelan, space is created for the evolution of traditional music that remains relevant amidst global musical developments.